A Study on Standardization and Parameters for Standardization of Crude Drugs: Exploring Standardization of Crude Drugs and its Parameters in Pharmacognosy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Raw pharmaceuticals are any naturally occurring, unprocessed material produced fromorganic or inorganic sources such as plant products, animal products and microbes for use in humanor other animal diagnosis, treatment, mitigation or prevention of sickness. Research in pharmacognosyrelies heavily on the discovery of crude drugs utilising their organoleptic characteristics. In light of this,the present study focuses on Crude Drug Standardization and Standardization Parameters in light ofthis fact.